Working Paper No. 63, On Karl Polanyi and His Conception of Fascism - Mistkawi, Serene (Working Papers in Economics, 2022)
This inquiry seeks to establish that the writings of author Karl Polanyi offered insights into key variables and historical conditions that gave rise to the system we know of as “fascism.” Integral to his insights, Polanyi describes economic conditions attendant for fascism to emerge, with one condition noted as widespread and persistent unemployment. Polanyi stresses that fascism needs to be understood as reactionary, a responding to features integral to classical liberalism. Considering a broad historical context Polanyi teaches us of the political conditions necessary for fascism to emerge and take form as political movements wielding power. He considers conflicts in aims between economic and political institutions. In addition, Polanyi analyzes some implications of a changing market, as well as some effects that a changing market might have over individual freedoms, as well as some of the complexities that can be associated with regulation.
Economics
Keywords: classical liberalism; currency; fascism; interventionism; regulation

Karl Polanyi’s ‘socialist accounting’ and ‘overview’ in the age of data analytics - Rief, Silvia (New Political Economy, 2022)
Digital capitalism’s information infrastructure is the subject of contentious debates concerning its transformative effects on the political economy and society. A frequent proposition, referring to older arguments of the ‘socialist calculation debate’, is that with big data analytics the pro-market arguments of neoliberal economists such as Hayek or Mises become obsolete. This article critically examines this proposition by drawing on Karl Polanyi’s notion of overview; a core theme in his outlines of a socialist economy and accounting written in the 1920s. In these contributions to the early Austrian socialist calculation debate, Polanyi discusses how to gain knowledge of the economic and social processes in such a way that the economy can be democratically governed according to its socialist aims and purposes. This article highlights the relevance of Polanyi’s work on socialist accounting, along with his later perspectives on technology and on social scientific method, for reflecting upon data- and algorithm-driven economic governance. Polanyi’s critical analysis of abstraction effected through methods of knowing suggests a sceptical stance vis-à-vis current versions of technological ‘solutionism’, which places its faith in data and algorithms as tools for economic and social, or socialist, planning.
Sociology; Economics
Keywords: Karl Polanyi; accounting; data analytics; digital socialism; economic theory; overview; socialist accounting; socialist calculation

Polanyi and social economy - Isaac, Barry L. (A Handbook of Economic Anthropology, 2022)
Substantivism stemmed from the writings of Hungarian lawyer-turned-historian Karl Polanyi, who argued that capitalism is a historically unique kind of economy that is disembedded from the social matrix. By implication, the socially embedded pre-capitalist economies studied by anthropologists, historians and classicists cannot be understood using the formal economics developed to analyze capitalist economies. Rather, new tools for analysing their 'substantive' economies must be employed. Substantivism was championed in economic anthropology by economist-turned-anthropologist George Dalton and became the reigning paradigm in the subfield during the 1960s. Formalism arose in opposition, arguing that capitalist and pre-capitalist economies differ in degree, not in kind, and thus can all be analysed using the tools of microeconomics. Formalism largely displaced substantivism during the 1970s and 1980s as anthropologists increasingly focused on the economic integration of the world's peasant sectors into their national and regional economies.
Economics; Anthropology

Devlet, Piyasa ve Toplum: Karl Polanyi ve Friedrich A. Hayek Üzerine Bir İnceleme - Güder, Mustafa; Atalay, Kürşad (İzmir İktisat Dergisi, 2022)
Individual life in general; It is determined by political, economic and sociological structures. The main forces that shape these structures are the state, market and society, respectively. When the views of Karl Polanyi and Friedrich Hayek on the state, market and society are considered comparatively, a holistic approach can be reached for understanding human life. In this context, the two thinkers have been the pioneers of two opponents lines in social sciences by putting forward opposite perspectives on the same phenomena. In the study, it is determined that these thinkers have a descriptive power in the ideological classification of later studies. Based on this, the views of the thinkers; It is put forward that it represents an "ideological pH value" for the social sciences. Polanyi draws attention that the ideals of individual freedom and equality claimed by the market system are not realized; brings social values to the fore.. Hayek claims that the market is the best institutional order that ensures human well-being and freedom. This study aims to discuss Hayek's free market view and Polanyi's embedded economic system with its political, economic and social aspects comparatively.
Economics
Keywords: HAYEK; Friedrich A. von (Friedrich August); 1899-1992; devlet; market; piyasa; society; state; toplum

The political trilemma of contemporary social-ecological transformation – lessons from Karl Polanyi’s The Great Transformation - Novy, Andreas (Globalizations, 2022)
This article advances Rodrik's political trilemma of the world economy by using insights from Polanyi’s The Great Transformation, which helps to grasp the interwoven dynamics of long-term transformations due to climate change and geopolitical reordering on one hand, and on the other short-term political ruptures due to countermovements. Rodrik's globalization trilemma shows the incompatibility of hyperglobalization with the need for an enlarged democratic policy space. Its nodes (globalization, nation state and democracy), however, have to be redefined to grasp contemporary dynamics of deglobalization. Based on a modified political trilemma of contemporary social-ecological transformation, I discuss and compare three visions and the resultant strategies: (1) Liberal globalism, focusing on hyperglobalization and individualism, (2) nationalistic capitalism, stressing national sovereignty and authoritarian governance, and (3) foundational economy based on planetary coexistence which combines selective economic deglobalization with a strengthening of a place-based foundational economy, and their respective social-ecological infrastructural configurations.
Political Science; Economics
Keywords: Great Transformation; The (Book); Polanyi; deglobalization; foundational economy; hyperglobalization; social-ecological transformation

Discussions around Argentine Capitalism: Economic Debate and Contribution of Karl Polanyi for Our Days - Rossi, Ignacio Andrés (2022)
The article proposes to address the current discussions about national capitalism and the Argentine economy from a set of canonical ideas of the work of Karl Polanyi. Argentina, which for several decades has been going through recurring crises in its economic model, awakens a plurality of voices from social scientists and specialized journalists who debate the problems, limitations and projections of national capitalism. For this, we have surveyed these discussions, to a greater extent, from the specialized press and the recently published bibliography, paying attention to the theoretical, interpretative and ideological proposals that allow us to generate relationships with Polanyi's theory. It was concluded that the latter's ideas about the functioning of capitalism, markets, the State and contemporary social dynamics provide significant conceptual background to frame the current discussions among social scientists about the Argentine economy.
Economics
Keywords: Argentina; capitalism; development; stability; state